THE ASSOCIATION OF UNINTENDED PREGNANCY WITH STUNTING ON CHILDREN UNDER FIVE YEARS OLD: A SYSTEMATIC REVIEW - Annisa Lidra Maribeth; Ahmad Syafiq (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Introduction: One of the complex causes of stunting is an unintended pregnancy. Children from unintended pregnancies are at greater risk for stunting than children born from intended pregnancies. This study aims to analyze the association of intended pregnancies with stunting events in children under 5 years old. Methods: This systematic review used PRISMA-P protocol (Preferred Reporting Items for Systemic Review and Meta-Analysis Protocols) in 2009. Studies were collected through search in the source data Scopus, Google Scholar, PubMed from January 2015 through May 2018. Keywords search used PICOS (Population Intervention Compare Outcome-Study design) technique. 278 studies were found and five studies were included in this study. Results: From the 5 studies reviewed, it was found that unintended pregnancies can be the cause of stunting in the range 1.25 to 2.19 times higher than the intended pregnancy. Conclusion: We found a significant relationship between unintended pregnancies among 5 countries (Bangladesh, Nepal, India, Northern Malawi, and Indonesia) with stunting in children under 5 years’ old.